Mechanical and fatigue properties of CFRP plate reinforced steel structural interface - Hua Zhu (Functional Materials, 2018)
The carbon fiber-reinforced polymer (CFRP) has high strength, low weight and corrosion resistance. In addition, CFRP can improve the fatigue properties of steel products. In this work, we study the mechanical and fatigue properties of a steel plate hardened with carbon fiber. Tensile studies with pressure control were carried out on a plate of steel reinforced with carbon fiber using an electro-hydraulic servo-amplifier machine for testing materials MTS810. Tests for fatigue strength of cracked steel plate and CFRP alloy were carried out at different stress amplitudes. When checking the fatigue characteristics, an increase in the amplitude of the bending force resulted in a decrease in the fatigue life of the specimens. It has been found that the mechanical properties of a steel plate hardened with carbon fiber at equal loads are better than that of a steel plate, and the fatigue life is greater.